Solid-catalyzed transport limitations assessment in gas-phase conversion of ethanol to hydrogen over Ni-promoted MMT/TiO2 nano clay catalyst - Mulewa, William; Tunje Kadere, Titus (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Mass transport constraints were investigated as they relate to the conversion of ethanol to hydrogen in the gas phase over a Nickel-Montmorillonite/Titanium oxide nanoparticle catalyst. Catalyst synthesis was performed via a modified sol-gel/ impregnation method. Ethanol was dehydrated catalytically using a tube-shaped packed bed reactor while catalyst characterization was through FTIR, XRD, SEM-EDX, TGA, and BET analysis. The Weisz-Prater and Mears' criteria were analyzed theoretically, and the catalyst particle size and reactant flow rate were adjusted experimentally to determine transport limitations. The results demonstrate an absence of gas-phase and intra-particle diffusion limitations for catalyst pellet diameter . This is attributed to the high effectiveness factor  for particles obtained theoretically. Besides, the high fractional conversion  obtained experimentally is an indication of constant ethanol conversion because there are no limitations on mass transfer. Ni-promoted MMT/TiO2 nanoparticle catalyst offers great promise for use in ethanol steam reforming for selective and cost-effective hydrogen production, as can be deduced from the results presented here.
Keywords: Hydrogen; Ethanol conversion; Mass transfer limitation; Nanoclay catalyst; Effectiveness factor